PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Fitriani, Siti Rahmah; Nurdiniah, Dade (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
One of the industries that is impacted by macroeconomic factors is the transportation sector. A corporation's high company value is undoubtedly reflected in its good performance. In addition, the company's size affects its managerial capabilities and ability to provide services. Using company size as a moderating variable, the research aims to ascertain and examine the impact of financial performance on company value. Descriptive statistics, multiple regression analysis, classical hypothesis testing, and moderate regression analysis (MRA) are the analytical techniques employed in this study. Nine businesses in the transportation sector were chosen for this study sample using the purposive sampling technique. Research data was taken from the 2018”“2022 annual financial reports of transportation sector companies listed on the IDX. The research results show that financial performance as measured by profitability (ROA) and liquidity (CR) simultaneously has a positive effect on company value. Meanwhile, partially profitability (ROA) has a significant positive effect on company value. Liquidity (CR) has a significant negative effect on company value. Company size is able to moderate both partially and simultaneously the influence of profitability and liquidity on company value.